Analysis and Performance Evaluation of CLCC Applications in Key Power Transmission Channels - Kang Liu; Baohong Li; Qin Jiang (Energies, 2025)
The YZ-ZJ DC transmission project addresses significant power transmission challenges in a specific region’s power grid, which faces unique pressures due to overlapping “growth” and “transition” periods in energy demand. This study focuses on the integration of Controllable-Line-Commutated Converters (CLCCs) into the YZ-ZJ DC transmission project at the receiving end, replacing the traditional LCCs to mitigate commutation failures during AC system faults. The main innovation lies in the development of a hybrid electromechanical–electromagnetic simulation model based on actual engineering parameters that provides a comprehensive analysis of the CLCC’s electromagnetic characteristics and system-level behavior under fault conditions. This is a significant advancement over previous research, which mainly focused on discrete electromagnetic modeling in ideal or simplified scenarios without considering the full complexity of real-world regional power grids. The research demonstrates that integrating CLCCs into the regional power grid not only prevents commutation failures but also enhances the overall reliability of the transmission system. The results show that CLCCs significantly improve fault tolerance, stabilize power transmission during faults, reduce power fluctuations in neighboring transmission lines, and enhance grid stability. Furthermore, this study confirms that the CLCC-based YZ-ZJ DC project outperforms the traditional LCC system, maintaining stable power transmission even under fault conditions. In conclusion, this study validates the feasibility of CLCCs in resisting commutation failures when integrated into a large power grid and reveals their positive impact on the regional grid.